Kad Hari Raya - Abdul Karim, Hassan Basri; Abdullah, Harishah (Nil, 1995)
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada Hj. Hassan Basri Abdul Karim dan Hjh. Che Harishah Abdullah